Circulating metabolite signatures indicate differential gut-liver crosstalk in lean and obese MASLD - Mathias Haag; Stefan Winter; Aurino M. Kemas; Julia Tevini; Alexandra Feldman; Sebastian K. Eder; Thomas K. Felder; Christian Datz; Bernhard Paulweber; Gerhard Liebisch; Oliver Burk; Volker M. Lauschke; et al. (JCI Insight, 2025)
BACKGROUND. Alterations in circulating metabolites have been described in obese metabolic dysfunction-associated steatotic liver disease (MASLD), but data on lean MASLD are lacking. We investigated serum metabolites, including microbial bile acids (BAs) and short-chain fatty acids (SCFAs), and their association with lean and obese MASLD. METHODS. Serum samples from 204 subjects of European descent were allocated to four groups: lean healthy (n=61), lean MASLD (n=49), obese healthy (n=47) and obese MASLD (n=47). LC/MS-based metabolomics was performed followed by linear model analysis. MASLD prediction was assessed based on LASSO regression. Functional effects of significantly altered molecules were confirmed in organotypic 3D primary human liver cultures. RESULTS. Lean MASLD was characterized by elevated isobutyrate, along with higher methionine sulfoxide, propionate and phosphatidylcholines. Patients with obese MASLD had increased sarcosine and decreased lysine and asymmetric dimethylarginine. Using metabolites, sex and body mass index, MASLD vs. healthy could be predicted with a median AUC of 86.5% and 85.6% in the lean and obese subgroups, respectively. Functional experiments in organotypic 3D primary human liver cultures showed that propionate and isobutyrate induced lipid accumulation and altered expression of genes involved in lipid and glucose metabolism. CONCLUSION. Our results indicate that lean MASLD is characterized by a distinct metabolite pattern related to amino acid metabolism, lipids and SCFAs, while metabolic pathways of lipid accumulation are differentially activated by microbial metabolites. Our findings highlight an important role of microbial metabolites in MASLD pathogenesis, with implications for the predictive and mechanistic assessment of liver disease across different weight categories. FUNDING. The work received funding from the Robert Bosch Stiftung, Stuttgart, Germany, the Swedish Research Council [grant numbers 2021-02801, 2023-03015 and 2024-03401], the ERC Consolidator Grant 3DMASH [101170408], Ruth and Richard Julin Foundation for Gastroenterology [grant number 2021-00158], the SciLifeLab and Wallenberg National Program for Data-Driven Life Science [WASPDDLS22:006], and the Novo Nordisk Foundation [NNF23OC0085944 and NNF23OC0084420]. JT was supported by PMU-FFF [grant number E-18/28/148-FEL].